SCRUB NURSE SCHEDULING SYSTEM IN HOSPITAL OPERATION THEATRE - MAHATHER, MARINA (IRC, 2020)
In medical field regardless government sector or private sector, having an efficient scheduling system for scrub nurses are still becoming a major problem to the hospitals. This is because many hospitals are still using a manual scheduling system which causes a lot of issues to these nurses. In order to resolve the issue, developing a systematic scheduling system is crucial for the nurses as they are one of the core entities in the hospital. This scheduling system will help the nurses to keep updated their weekly schedule as well as ease their processes to apply leave or changes. Therefore, the aim of this project is to ease the workload of head nurse to arrange the schedules for the staffs and to keep the nurses updated with their schedule despite their hectic working environment.